INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN MENULIS: TINJAUAN PUSTAKA - Nurfidah; Sastromiharjo, Andoyo (STKIP Siliwangi, 2024)
The use of digital technology in education has experienced rapid development, especially in teaching writing skills. This study aims to examine the impact of the use of digital technology on students' writing skills. This study uses a literature review method with content analysis techniques to identify and understand themes that emerge from relevant literature. Data sources are taken from journal articles published from 2019 to 2024, using strict inclusion and exclusion criteria. Quantitative analysis was carried out through a meta-analysis approach to calculate the magnitude of the impact of interventions reported in various studies. The results of the study indicate that the integration of digital technology has a significant positive impact on students' writing skills. The overall impact of 0.77 indicates a substantial increase in writing skills caused by the use of digital technology. In addition, digital technology also supports collaborative and inclusive learning, which is important in the context of modern education. The implications of this study are the importance of adopting and integrating digital technology in the education curriculum to improve students' writing skills. Recommendations provided include the development of technological infrastructure, teacher training, and the development of more adaptive and collaborative digital learning resources.